IgE-Mediated Food Allergy; Complications & Implications - - Lotfollah Behroo (Journal of Pharmacy and Nutrition Sciences, 2013)
IgE-mediated allergic diseases are a major socio-economic problem caused by complex interactions between genes and the environment. In general, the production of IgE and allergic inflammation result from overexpression of T-helper 2[(Th2); IgE-producing T-lymphocyte lineage] type immune responses (type I hypersensitivity reactions) cytokines. On the average, it is estimated that 30-40% of the world population are now, being affected by one or more allergic condition(s) of which food allergies, for the most part, account for this augmentation and consequently embrace a major portion of the affections(up to 20%). Of course, it should be noted that, the vast majority of reactions due to food allergy do not require hospitalisation and, thus, the true number of distinguished/reported cases is still, likely to be significantly higher. Virtually, any food protein can cause clinical syndrome in susceptible individual; however, only a small number of foods are responsible for more than 90 percent of allergic food reactions, and most patients are sensitive to fewer than three foods. In children, the most common foods causing reactions are egg, milk, peanuts, soy, wheat, tree nuts and fish. Adults most often react to peanuts, tree nuts, fish and shellfish. Despite allergy to food proteins having been known for many years, there is little information on whether food antigens are increased in these conditions and how much antigen is absorbed as well as, the biological activity of the absorbed allergen. One explanation could be the limitations of sensitive analytic methods for analyzing food proteins in human serum. On the other part, current curative cares under evaluation include strategies to block IgE or IgE synthesis and to interrupt the Th2-dependent allergic cascade. Altogether, the thing of noteworthy is that, a determined effort using the best appropriate food allergy diagnostic technics would be certainly required in order to, produce the most clinically effective/safe patient results and, develop any effectual/promising therapeutic approaches for IgE-mediated food allergies owing to their epidemic worldwide increase in prevalence and morbidity.